The Problem of Kundalini in the Context of Yogic Aspects of the Bengali Tantric Vaisnava (Sahajiya) Tradition - Czyżykowski, Robert (Religions of South Asia, 2019)
This article investigates the possible existence of the concept of kundalini in medieval Bengali Tantric Vaissava Sahajiya tradition. Various source materials from Vaisnava Sahajiya literature which might refer to the popular Tantric concept kundalini are esoteric and very obscure. Nevertheless, the concept of kundalini probably was not completely absent from Eastern Indian Tantric Vaisnava sources, though it was not very prominent and did not play as crucial a role as in many Saiva-Sakta traditions. It functioned more on a structural level, for example, the ’crooked river’ (banka nadi) from the Yogic subtle body physiology of the Vaisnava Sahajiyas might be viewed as an equivalent of the kundalini concept. Other possibilities are also critically analysed, particularly the figure of Gandhakali as suggested by P. Dasa.